Competitive Package Formation Policy of International Loads Transportation Services in Lithuania - Vengrauskas, Vytautas Petras; Langvinienė, Neringa (Ekonomika, 2003)
International load transportation by road is one of the most perspectives field for Lithuanian business enterprises, orienting them business to European market. Increasing turnover in load transportation shows not congest market However after Lithuania enter to EU, a competition between transporter and expedition firms will increase. It is necessary to analyze methods how to detaur them business for staying in the competition between local and European transporters. This theme is rather new. Interest in international load transportation was very low. Thought transport services are one of the few, that arc analyzed by our economists, these data are rather fragmentary and do not reflect a specific of these services. Scientific problem is formulated in such way: that should include into international load transportation package, which should give a quality for a customer, what policy of package formation should be. An object - international load transportation service A subject international load transportation service’s package formation. A goal - to present the essential theoretical aspects of international load transportation: definition, classifying system, policy of package formation. The main conclusions: International load transportation service is a service, that services supplier by technical equipment support supplies for international load transportation customer. This service is supplied after consultations with customer, regarding to specific demand of customer. This service gives an opportunity to get a load “from door to door”. International load transportation service could be c1assified as business services, as distribution services and as transportation services, too. International load transportation service package - a package, that satisfy the primary and secondary needs of customers - load transporting, grouping, sorting, storing and etc. Lithuanian international load transportation services enterprises a priority should give for qualitative international load transportation services package formation, Lc. adequate policy of package formation in the competition circumstances in EU. Here are theoretical aspects of international load transportation services: conception of these services, peculiaritics of services package formation politics; practices of formatting competitive services package of Lithuanian firms, what arc specialized in international load transportation, orienting them business to European market, in this article.